The relationship between gut microbiota and neonatal pathologic jaundice: A pilot case-control study - You, Jia Jia; Qiu, Jun; Li, Gui Nan; Peng, Xiao Ming; Ma, Ye; Zhou, Chang Ci; Fang, Si Wei; Huang, Rui Wen; Xiao, Zheng Hui (Frontiers in Microbiology, 2023)
Abstract Background and Objective: Neonatal jaundice is a common clinical disease in neonates. Pathologic jaundice is more harmful to neonates. There are a few studies on the biomarkers of pathologic jaundice and the correlation between gut microbiota and clinical indices. We aimed to reveal the characteristics of gut microbiota in pathologic jaundice, provide potential biomarkers for the diagnosis of pathologic jaundice, and find the correlation between gut microbiota and clinical indices. Methods: Fourteen neonates with physiologic jaundice were recruited into a control group (Group A). Additionally, fourteen neonates with pathologic jaundice were recruited into a case group (Group B). The microbial communities were analyzed using 16S rDNA sequencing. LEfSe and the differences in the relative abundance of gut microbiota were used to identify different bacteria within the groups. The ROC curve was used to assess effective biomarkers for pathologic jaundice. Spearman’s rank-sum correlation coefficient was used to evaluate the correlation between gut microbiota and clinical indices. Results: There were no differences in the total richness or diversity of gut microbiota between the two groups. At the phylum and genus levels, compared with the physiologic jaundice group, Bacteroidetes (P=0.002) and Braydrhizobium (P=0.01) were significantly higher, while Actinobacteria (P=0.003) and Bidfldobacterium (P=0.016) were significantly lower in the pathologic jaundice group. Bacteroidetes were valuable in differentiating pathologic jaundice from physiologic jaundice by the ROC curve, and the area under the ROC curve (AUC) value was 0.839 (95%CI (0.648~0.995)). In the pathologic jaundice group, Bacteroidetes were negatively associated with total bilirubin (TBIL) (P<0.05). In the physiologic jaundice group, Bacteroidetes were positively associated with TBIL(P<0.05). Conclusion: Bacteroidetes can be used as biomarkers to identify pathologic jaundice. And Bacteroidetes are positively associated with bilirubin levels.